(untitled) (Medico Legal Update, 2019)
Background/Objectives: The purpose of this study was to verify the moderated mediation effect of grit on the mediating effect of growth mindset in the relationship between employment stress and happiness in 364 college students in Korea. Method/Statistical Analysis: For statistical analyses, reliability analysis, correlation analysis, and moderated mediation effect analysis were performed using SPSS Win.21.0 and PROCESS macro for SPSS version 3.2. Findings: The results of the study showed a statistically significant correlation between happiness and growth mindset and grit. Employment stress was negatively correlated with happiness, growth mindset, and grit. In addition, the grit of college students moderated the relationship between employment stress and happiness via the growth mindset. Improvements/Applications: These results will be used as a new model for grit to control the emotional stress of college students through the growth mindset.